Bacteriophage typing of coagulase-negative staphylococci. - Jefferson, S J (1979)
Cultures comprising the 10 species of coagulase-negative staphylococci proposed by Kloos and Schleifer (J. Clin. Microbiol. 1:82--88, 1975) were typed with bacteriophages isolated from Staphylococcus epidermidis. Although only 10.5% were typable, 50% of those identified as S. epidermidis were typed. Cultures from patients with middle ear infections were also classified by this system and phage typed.